Alkannin, HSP70 inducer, protects against UVB-induced apoptosis in human keratinocytes. - Yoko Yoshihisa (Public Library of Science (PLoS), 2012)
Alkannin is an active constituent from the root extract of Alkanna tinctoria of the Boraginaceae family and it may have utility as a heat shock protein 70 (HSP70) inducer in living organisms. Here, the effects of alkannin-induced HSP70 on ultraviolet (UV) B (40 mJ/cm(2))-induced apoptosis were investigated in human keratinocyte HaCaT cells. Pretreatment of cells with alkannin (1 µM) caused significant inhibition of UVB-induced apoptosis and caspase-3 cleavage. On the other hand, the addition of KNK437 (HSP70 inhibitor) reversed the action of alkannin increasing UVB-induced apoptosis in a dose-dependent manner. In addition, differences in gene expression associated with the suppression of UVB-induced apoptosis in the presence of alkannin were investigated using Gene Chip assay. Our results indicate that alkannin suppresses UVB-induced apoptosis through the induction of HSP70 in human keratinocytes, and therefore, we suggest the usefulness of using alkannin as an antiaging agent.